To a question about the necessity and indications for genetic screening in obstetric and gynecological practice - K. N. Grigoreva; E. G. Demianovskaya; V. O. Bitsadze; J. Kh. Khizroeva; N. R. Gashimova; E. V. Slukhanchuk; I. S. Kalashnikova (Акушерство, гинекология и репродукция)
Here, we discuss an importance and necessity of genetic research in work of an obstetrician-gynecologist of primary health care upon providing medical care. Infertility, habitual miscarriage, the birth of children with congenital malformations greatly affects psycho-emotional state of both women and men, which is why every practicing doctor needs to have at least minimal knowledge about genetic research to prevent/warn negative consequences of certain conditions. We believe that an issue on genetic testing should arise at the stage of preconceptional preparation/in the first trimester of pregnancy, because it is the most favorable period for prevention of multiple conditions.